Effect of Donor Sperm on Quality of Life in Patients with Severe Oligoasthenosperm After ICSI Failure - Wang K; Xu Y; Qin N; Guo Y; Bai J; Li Z (Journal of Multidisciplinary Healthcare)
Ke Wang,1– 3,* Yan Xu,2,3,* Ningxin Qin,1 Yi Guo,1 Jie Bai,3 Zheyuan Li4 1Center of Reproductive Medicine, Shanghai Key Laboratory of Maternal Fetal Medicine, Shanghai Institute of Maternal-Fetal Medicine and Gynecologic Oncology, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 2Department of Nursing, Shanghai Sanda University, Shanghai, 201209, People’s Republic of China; 3School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 4Intensive Care Unit, Zhongshan Hospital, Fudan University, Shanghai, 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ningxin Qin, Email ningxinqin@51mch.comObjective: To explore the effects of donor sperm on reproductive quality of life, sleep quality and erectile function in patients with severe oligoasthenospermia after the failure of intracytoplasmic sperm injection (ICSI), and to provide targeted reference for intervention.Methods: From January 2021 to December 2023, patients with severe oligoasthenospermia who received assisted pregnancy treatment in Obstetrics and Gynecology Hospital Affiliated to Tongji University were selected as the study objects. Among them, 82 cases using sperm donor assisted pregnancy after ICSI failure were set as the observation group, and 82 cases using propensity score 1:1 matching ICSI failure after ICSI assisted pregnancy were set as the control group. The levels of serum total testosterone, reproductive quality of life, sleep quality and erectile function of the two groups were compared using the general data questionnaire, FertiQoL, Pittsburgh Sleep Quality Index (PSQI) and International erectile Function Index − 5(IIEF-5).Results: There was no significant difference in social demographic data and serum total testosterone level between the two groups after matching propensity score (P> 0.05). The total score of FertiQoL and PSQI in the observation group were higher than those in the control group, and the incidence of erectile dysfunction was higher than that in the control group, with statistical significance (P< 0.05).Conclusion: The use of donor sperm for pregnancy after ICSI failure in patients with severe oligoasthenospermia has a great impact on their reproductive life, sleep quality and erectile function. Medical staff should pay attention to the quality of life and erectile function of these patients, and formulate targeted measures to help these patients cope positively.Keywords: severe oligoasthenospermia, supply semen, erectile function, reproductive life quality, sleep quality